Broadening the phenotype of the TWNK gene associated Perrault syndrome - Bálint Fekete; Klára Pentelényi; Gabor Rudas; Anikó Gál; Zoltán Grosz; Anett Illés; Jimoh Idris; Gabor Csukly; Andor Domonkos; Maria Judit Molnar (BMC, 2019)
Abstract Background Perrault syndrome is a genetically heterogenous, very rare disease, characterized clinically by sensorineural hearing loss, ovarian dysfunction and neurological symptoms. We present the case of a 33 years old female patient with TWNK-associated Perrault syndrome. The TWNK gene is coding the mitochondrial protein Twinkle and currently there are only two reports characterizing the phenotype of TWNK-associated Perrault syndrome. None of these publications reported about special brain MRI alterations and neuropathological changes in the muscle and peripheral nerves. Case presentation Our patients with TWNK-dependent Perrault syndrome had severe bilateral hypoacusis, severe ataxia, polyneuropathy, lower limb spastic paraparesis with pyramidal signs, and gonadal dysgenesis. Psychiatric symptoms such as depression and paranoia were present as well. Brain MRI observed progressive cerebellar hyperintensive signs associated with cerebellar, medulla oblongata and cervical spinal cord atrophy. Light microscopy of the muscle biopsy detected severe neurogenic lesions. COX staining was centrally reduced in many muscle fibers. Both muscle and sural nerve electron microscopy detected slightly enlarged mitochondria with abnormal cristae surrounded by lipid vacuoles. In the sural nerve, dystrophic axons had focally uncompacted myelin lamellae present. Genetic investigation revealed multiple mtDNA deletion and compound heterozygous mutations of the TWNK gene (c.1196 A > G, c.1358 G > A). Conclusion This study demonstrates that TWNK associated Perrault syndrome has a much broader phenotype as originally published. The coexistence of severe hypoacusis, spastic limb weakness, ataxia, polyneuropathy, gonadal dysgensia, hyperintense signals in the cerebellum and the presence of the mtDNA multiple deletion could indicate the impairment of the TWNK gene. This is the first report about pyramidal tract involvement and cerebellar MRI alteration associated with TWNK-related Perrault syndrome.